2013
DOI: 10.1111/jog.12014
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome and clinical features of monochorionic monoamniotic twin gestation

Abstract: Perinatal outcomes in our study were relatively good irrespective of high frequency of cord entanglement. Close fetal monitoring may allow MM twin pregnancies to extend gestational age, which may contribute to reduce both fetal death and neonatal morbidity by immaturity, although the best delivery weeks remained undetermined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
(80 reference statements)
5
22
0
Order By: Relevance
“…Studies before the 1990s reported a mortality rate above 40% in such twins [1]. Our previous study found an overall survival rate of 75% in monoamniotic twins, not counting those with fetal malformations or reversed twin arterial perfusion sequence [7], which was consistent with results found by Hack et al [5] in their study of monoamniotic twin mortality during the previable period. However, recent studies have reported improved perinatal survival rates.…”
Section: Recent Improvements In Perinatal Outcomesupporting
confidence: 88%
See 2 more Smart Citations
“…Studies before the 1990s reported a mortality rate above 40% in such twins [1]. Our previous study found an overall survival rate of 75% in monoamniotic twins, not counting those with fetal malformations or reversed twin arterial perfusion sequence [7], which was consistent with results found by Hack et al [5] in their study of monoamniotic twin mortality during the previable period. However, recent studies have reported improved perinatal survival rates.…”
Section: Recent Improvements In Perinatal Outcomesupporting
confidence: 88%
“…Most deaths were caused by compromised fetal circulation due to umbilical cord entanglement or by congenital malformations, the latter being present in up to 26% of monoamniotic pregnancies [12]; complications commonly seen in diamniotic twins, such as twin-twin transfusion syndrome, seem to be less frequent in monoamniotic twins [5,7,8 & ,13,14]. Our recent study found a perinatal mortality rate of 2% among monoamniotic twins, excluding those with fetal malformations and those who were lost before becoming viable [7], which was similar to rates reported by Allen et al [3] and Baxi and Walsh [15] (2.8 and 2.4%, respectively). Our previous study found an overall survival rate of 75% in monoamniotic twins, not counting those with fetal malformations or reversed twin arterial perfusion sequence [7], which was consistent with results found by Hack et al [5] in their study of monoamniotic twin mortality during the previable period.…”
Section: Recent Improvements In Perinatal Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…ine and neonatal death with perinatal mortality ranging between 10 and 40%. [1][2][3][4][5][6] This high perinatal mortality rate is partially the result of an increased incidence in congenital anomalies (up to 26%) 1 as well as to twin-reversed-arterial-perfusion sequence and conjoined twinning. 7 Another contributor to perinatal mortality in monoamniotic twins is the fact that two fetuses share a single placenta and a single amniotic cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Murata et al (2013) 21 studied perinatal outcome of monochorionic monoamniotic twin gestation. In the study of 38 MM twin pregnancies (76 fetuses), the perinatal mortality rate was 2%and the neuro morbidity rate was 8% The overall survival rate was 75%.…”
Section: Discussionmentioning
confidence: 99%